Bronchial Blocker Entrapment in a 7-Month-Old Infant: A Case Report. Issue 3 (November 2020) - Templeton, T. Wesley; Petty, John K.; Sutton, Cameron J.; Goenaga-Díaz, Eduardo J.; Templeton, Leah B.
Abstract : We present the case of a 7-month-old infant undergoing thoracotomy and left lower lobe lobectomy who experienced a significant complication related to lung isolation with a bronchial blocker. Despite good isolation and seemingly appropriate positioning, the bronchial blocker became entrapped within the staple line at the bronchial stump. Fortunately, the surgeon was able to free the blocker. Going forward, we recommend clinicians be vigilant in positioning the blocker just distal to the carina in all cases and, further, consider retracting the blocker into the trachea before surgical intervention on the airway to avoid inadvertent entrapment of the device.